Dengue Infection in Pregnancy: Impact on Maternal and Fetal outcomes - Ishaq, Sadia; Khalil, Ayesha; Sethi, Sher Muhammad; Khatri, Adeel; Rehman, Atta Ur; Muhammad, Asif Jan; Khan, Muhammad Rashid Naseem (Infectious Diseases Journal of Pakistan, 2023)
Objective: To assess the impact of dengue infection during pregnancy on obstetric and fetal outcomes. Methodology: A retrospective study was conducted by Department of Medicine at a tertiary care hospital in Karachi, Pakistan by reviewing patient records from 2009 – 2015. Inclusion criteria were pregnant patients of any gestational age fulfilling WHO diagnostic criteria for dengue infection. Exclusion criteria were febrile pregnant patients positive for malaria parasite, immunological tests for malaria or with positive blood cultures, patients diagnosed with HELLP syndrome or other autoimmune disease and patients with drug-induced thrombocytopenia. Frequencies and percentages were noted for maternal and fetal outcomes being studied. Results: Our data shows that antenatal dengue infection has the potential to significantly impact maternal and fetal outcomes.Antepartum and postpartum hemorrhage each occurred in 5% of patients with acute antenatal dengue infection. Moreover, we note that counts may not be predictive of development of these complications, so extreme clinical vigilance is warranted. Oligohydroamnios occurred in 21% of our patients; this is likely to be a consequence of significant fluid shifts with dengue and hydration of the pregnant dengue patient is paramount. There may be an increased risk of fetal loss. Conclusion: Obstetric complications such as antepartum hemorrhage, oligohydramnios and postpartum hemorrhage can occur with acute dengue infection during pregnancy. Preterm delivery necessitated by these can impact neonatal outcomes (eg low birth weight and APGAR scores). Acute dengue infection contracted during the 3rd trimester carries high risk of causing pregnancy morbidity. As platelet counts are not predictive of development of bleeding complications, a high index of suspicion and extreme clinical vigilance are warranted. Keywords: Dengue; pregnancy; pregnancy complications; hemorrhage; premature birth